2013
DOI: 10.1016/j.athoracsur.2013.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular Finite Element Modeling of the Acorn CorCap Cardiac Support Device on a Failing Heart

Abstract: Background The Acorn CorCap Cardiac Support Device (CSD; Acorn Cardiovascular Inc, St. Paul, MN) is a woven polyester jacket that is placed around the heart and designed to reverse the progressive remodeling associated with dilated cardiomyopathy. However, the effects of the Acorn CSD on myofiber stress and ventricular function remain unknown. We tested the hypothesis that the Acorn CSD reduces end-diastolic (ED) myofiber stress. Methods A previously described weakly coupled biventricular finite element (FE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Nevertheless, our laboratory has found ED and ES LV pressure-volume relationships and mean myofiber stresses to be extremely valuable in evaluating the efficacy of novel medical and/or surgical procedures and devices for treating ischemic cardiomyopathies (5,9,21,22,31,33,36,38,40,48,54,58,59,61,64,65,70).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our laboratory has found ED and ES LV pressure-volume relationships and mean myofiber stresses to be extremely valuable in evaluating the efficacy of novel medical and/or surgical procedures and devices for treating ischemic cardiomyopathies (5,9,21,22,31,33,36,38,40,48,54,58,59,61,64,65,70).…”
Section: Discussionmentioning
confidence: 99%
“…Devices that wrap completely around the epicardium, and are made of synthetic materials, have been investigated and found to acutely reduce wall stress at the expense of reducing pump function. 32 …”
Section: Discussionmentioning
confidence: 99%
“…In the past, cardiac support devices, such as a woven polyester jacket and a nitinol mesh placed around the heart, were used in patients with severe heart failure. These clinical studies demonstrated prevention of further dilatation of the LV, promotion of reverse cardiac remodeling, and improvement in symptoms (6,28), which was likely attributable to reduced wall stress (29). The epicardial serpentine mesh also showed a beneficial effect to reduce wall stress in a postinfarct rat heart without worsening diastolic function.…”
Section: Discussionmentioning
confidence: 87%